Evaluation of General Entrepreneurship Programme Curriculum in Tertiary Institutions in Ogun State, Nigeria - Rasaq Ramota Ajoke; Ajisegiri Ruth O.; Afolari Eyitayo Rufus Ifedayo (Journal of Education Reseach and Evaluation, 2024)
Entrepreneurship programme has recently been discussed as the only solution to the unemployment ravaging the country. Using epistemological approach of the quantitative case study of the descriptive research design, this study assessed the general entrepreneurship programme curriculum in tertiary institutions in Ogun State. This was with a view to providing information on the extent of implementation of the entrepreneurship programme curriculum in Tertiary institutions in Ogun State, Nigeria. Directors of three higher institutions of learning (one University, one Polytechnic and one College of Education) were purposively selected based on compliance with the requirements for entrepreneurship programme. The results showed that the entrepreneurship programme curriculum in tertiary institutions in Ogun State was not effectively implemented.  Also, it was discovered that only 37.4% of the courses had written curriculum. In addition, it was discovered that only 35.4% written curriculum are available for the entrepreneurship programme courses. Based on the findings of the study, it was therefore recommended that more skill acquisition courses should be embraced as stipulated by the federal government and experts should be employed to design written curriculum for entrepreneurship courses in tertiary institutions in Ogun state among others.